On Linear and Nonlinear Fourth-Order Eigenvalue Problems with Nonlocal Boundary Condition - Dongming Yan (Journal of Function Spaces and Applications)
We determine the principal eigenvalue of the linear problem ,  , , where and . Moreover, we investigate the existence of positive solutions for the corresponding nonlinear problem. The proofs of our main results are based upon the Krein-Rutman theorem and fixed point index theory.